2017
DOI: 10.1111/azo.12213
|View full text |Cite
|
Sign up to set email alerts
|

Description of the immature stages of two Mononychus species (Coleoptera: Curculionidae: Ceutorhynchinae) and a study of the host preferences of M. punctumalbum for Iris species in central Europe

Abstract: Last larval instars and pupae of Mononychus punctumalbum (Herbst, 1784) and Mononychus schoenherri Kolenati, 1859 (Curculionidae, Ceutorhynchinae) are described in detail for the first time. No immatures of other species of this genus had previously been described. The immatures of Mononychus were compared with available data on immatures of all genera in the subfamily Ceutorhynchinae. Both the larvae and pupae of the two Mononychus species are very distinctive, having distinct characters from other genera in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 19 publications
(53 reference statements)
0
7
0
Order By: Relevance
“…It is worth emphasising that intensive M. punctumalbum feeding on flowers in natural habitats may lead to damage to the reproductive organs of the flower and limit the generative reproduction of plants, thereby leading to reduction of their population. This issue seems important in light of our earlier findings that the generative reproduction of some European irises, e.g., I. spuria L., I. sibirica L., and I. pseudacorus L., is impaired by M. punctumalbum foraging (Skuhrovec et al, 2018). The authors of the work suggest that bumblebees are the best pollinators of throated-type flowers.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…It is worth emphasising that intensive M. punctumalbum feeding on flowers in natural habitats may lead to damage to the reproductive organs of the flower and limit the generative reproduction of plants, thereby leading to reduction of their population. This issue seems important in light of our earlier findings that the generative reproduction of some European irises, e.g., I. spuria L., I. sibirica L., and I. pseudacorus L., is impaired by M. punctumalbum foraging (Skuhrovec et al, 2018). The authors of the work suggest that bumblebees are the best pollinators of throated-type flowers.…”
Section: Discussionmentioning
confidence: 90%
“…Flowering of I. aphylla in 2016-2018 Mean values ± SD are given. Means within columns with the capital letter ( A ) do not differ significantly between the years based on Tukey's test at α = 0.05.…”
mentioning
confidence: 99%
“…The capsule wall thickness and seed wall thickness had the greatest influence on the first principal component defining I. aphylla ( Figure 4 and Figure 5 ). The examination of the morphology of seed capsules conducted by Skuhrovec et al [ 22 ] demonstrated that the weevil was not able to pierce the I. aphylla capsule due to its thickness, as the insect’s mouthparts are much shorter than the capsule wall thickness.…”
Section: Resultsmentioning
confidence: 99%
“…However, observations conducted in 2017 confirmed these reports only in the case of I. sibirica . They demonstrated that the weevil pierced seed capsules, which were a source of nutrients during insect development [ 22 ]. In the case of I. aphylla , the weevil foraged only on flowers and did not damage the seeds [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…This species has a wide distribution in the central and western Palearctic region, where it is recognized as an important factor limiting Iris spp. populations (Skuhrovec et al, 2017). All Mononychus species are known to develop exclusively on Iris spp.…”
Section: Candidate(s) Prioritizationmentioning
confidence: 99%